The bigger bang - Lidsey, James E (Cambridge University, 2013)
James Lidsey steers us on a journey to the cutting edge of cosmology. Step-by-step, we travel back in time through Lidsey's book until we arrive at the very origin of the universe. There we look at the fascinating ideas scientists are currently developing to explain what happened in the first billion, billion, billion, billionth of a second of the universe's existence - the 'inflationary' epoch. Along the way, we are given accounts of many topics in theoretical cosmology, including the latest ideas on superstrings, parallel universes, and the ultimate fate of our universe. We also discover how the world of the very small (described by the physics of elementary particles) and the world of the very large (described by cosmology) are inextricably linked by events which wove them together in the first few moments of the universe's history.